2009
DOI: 10.1128/cvi.00238-09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus 16 and 18 Neutralizing Antibodies in Prenatal Women in British Columbia

Abstract: Human papillomavirus (HPV) type 16 and 18 neutralizing antibody (NAb) titers were measured in 1,020 prenatal women in British Columbia aged 15 to 39. HPV 16 and 18 NAbs were detected in 183/1,020 (17.9%) and 97/1,020 (9.5%), respectively, and 39 (3.8%) had NAbs to both types. Titers were similar across age strata.Measurement of type-specific antibody responses to human papillomavirus (HPV) is important for seroprevalence estimates and assessment of vaccine efficacy. Vaccine manufacturers have developed enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…Rates of cervical intraepithelial neoplasia (CIN) 21 for each age stratum (15)(16)(17)(18)(19)(20)(21)(22) in the calendar years 2004-2012 for the province of British Columbia were obtained from the BC Cancer Agency's population-based cervical cancer program. Incidence rate ratios (IRR) of CIN21 were described and compared before and after HPV vaccine program introduction in cohorts born in vaccine eligible years, and in non-vaccine eligible years using piece-wise Poisson regression analysis, and adjusted for age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of cervical intraepithelial neoplasia (CIN) 21 for each age stratum (15)(16)(17)(18)(19)(20)(21)(22) in the calendar years 2004-2012 for the province of British Columbia were obtained from the BC Cancer Agency's population-based cervical cancer program. Incidence rate ratios (IRR) of CIN21 were described and compared before and after HPV vaccine program introduction in cohorts born in vaccine eligible years, and in non-vaccine eligible years using piece-wise Poisson regression analysis, and adjusted for age.…”
mentioning
confidence: 99%
“…16 The program has also reported on HPV prevalence in British Columbia prior to the HPV vaccine implementation in women and men, 17,18 and assessed rates of HPV seropositivity in women receiving prenatal care. 19 To evaluate the impact of the HPV vaccine in the province, we used data from British Columbia's centralized cervical cancer screening program (CCSP) to report on the ecological trends in cervical intraepithelial neoplasia (CIN) 2 and CIN21 in young women aged 15-22 years before and after the implementation of the provincial HPV vaccine program.…”
mentioning
confidence: 99%
“…Conventional NAb assays for HPV are not feasible because of the inability of HPV to replicate in conventional cell cultures. This has been overcome by the use of HPV pseudoviruses (PsV) containing a reporter plasmid which is expressed when the PsV infect susceptible cells (1,10). NAb prevent PsV from infecting cells and expressing the reporter gene product.…”
mentioning
confidence: 99%
“…In this study, we compare HPV 16 and HPV 18 antibody responses at 7 months in cohorts of females enrolled in an ongoing 2-versus 3-dose Q-HPV vaccine trial (4), using both the Merck cLIA and an in-house PsV NAb assay (10).…”
mentioning
confidence: 99%
“…In a seroprevalence study based on a sample of 1020 agestratified anonymous sera from women 15 to 39 years of age in BC undergoing prenatal testing, (5) HPV type 16 and 18 antibodies were detected in 17.9% and 9.5% of subjects respectively, and 3.9% had antibodies to both types. Based on age-stratified data, the authors concluded that exposure to HPV types 16 and 18 occurred at a young age.…”
Section: Iii1 Femalesmentioning
confidence: 99%